1995
DOI: 10.4319/lo.1995.40.2.0263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of products released by Aphanizomenon flos‐aquae and purified saxitoxin on the movements of Daphnia carinata feeding appendages

Abstract: Experiments were run to determine the effect of filtrate from incubated Aphanizomenonflos-aquae on the thoracic appendage beat rate and frequency of postabdominal rejections by Daphnia carinata. Comparisons were made between the response to Aphanizomenon filtrate and to purified saxitoxin (STX). The short-term response pattern to the filtrate included an immediate 30-50% depression of thoracic appendage beat rate and elevation of postabdominal rejection rate followed by slowly decreasing thoracic appendage bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 18 publications
4
48
0
1
Order By: Relevance
“…We initially hypothesized that Lyngbya would be resistant to herbivory by amphipods in light of the negative effect of cyanobacterial neurotoxins on zooplankton (Haney et al 1995). As predicted, amphipods consumed more live Rhizoclonium than Lyngbya, decreasing Rhizoclonium growth while stimulating Lyngbya growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We initially hypothesized that Lyngbya would be resistant to herbivory by amphipods in light of the negative effect of cyanobacterial neurotoxins on zooplankton (Haney et al 1995). As predicted, amphipods consumed more live Rhizoclonium than Lyngbya, decreasing Rhizoclonium growth while stimulating Lyngbya growth.…”
Section: Discussionmentioning
confidence: 99%
“…Most freshwater cyanobacterial secondary metabolites can be grouped into two classes of toxins on the basis of their mode of biological activity: hepatotoxins (e.g., microcystins) and neurotoxins, such as paralytic shellfish poisons (PSPs; e.g., saxitoxin (STX) and anatoxin; Carmichael 1994; Kaebernick and Neilan 2001). Previous studies have demonstrated that PSPs can alter the feeding behavior and survivorship of freshwater zooplankton (Haney et al 1995;Gilbert 1996). However, the effects of PSPs on larger freshwater invertebrates, particularly mesograzers capable of consuming filamentous cyanobacteria, remain largely unexplored.…”
mentioning
confidence: 99%
“…Chemical cues seem more promising as daphnids have often been shown to respond to a variety of such cues. For example, Haney et al (1995) showed that exudates of toxic cyanobacteria lead to an immediate reduction of feeding behavior in D. carinata, and that after the exudates were removed, feeding returned to normal. This and other behaviors, such as predator-induced vertical migration in daphnids, clearly demonstrate chemically mediated behavioral responses (see review by Larsson and Dodson 1993).…”
Section: Discussionmentioning
confidence: 99%
“…HAB toxins easily fit these criteria and each may have evolved to play an active role in one or more intrinsic and (or) extrinsic functions. For instance, saxitoxins, the etiological agent of PSP may play an intrinsic role in DNA metabolism (Mickelson and Yentsch 1979;Anderson and Cheng 1988), or N storage (Anderson et al 1990b), and (or) an extrinsic role as an antipredation compound (White and Maranda 1978;Haney et al 1995). The precise evolutionary pressure(s) driving the synlhesis of each HAB toxin remains enigmatic, in large part because the toxins are chemically distinct ( Fig.…”
Section: Hab Toxins As Secondary Metabolitesmentioning
confidence: 99%